2016
DOI: 10.18632/oncotarget.13324
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic silencing of TET2 and TET3 induces an EMT-like process in melanoma

Abstract: Epithelial-Mesenchymal Transition (EMT) is a critical step in the progression of cancer. Malignant melanoma, a cancer developed from pigmented melanocytes, metastasizes through an EMT-like process. Ten-eleven translocation (TET) enzymes, catalyzing the conversion of 5-methylcytosine (5mC) to 5-hydroxylmethylcytosine (5-hmC), are down regulated in melanoma. However, their roles in the progression and the EMT-like process of melanoma are not fully understood. Here we report that DNA methylation induced silencing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 37 publications
0
29
0
Order By: Relevance
“…027008-14 128(2) February 2020 possible involvement of the promoter methylation of the TET2 gene. The methylation of CpG islands in the promoter region of genes is a well-known inhibitory mechanism for down-regulation of gene and protein expression (Figueroa et al 2010;Gong et al 2017). The hypermethylation of TET1 gene has been found in multiple primary tumors (Li et al 2016), and DNMT3A-mediated methylation of TET2 and TET3 promoters has been implicated in the induction of the epithelial-mesenchymal transition-like process and metastasis in melanoma (Gong et al 2017).…”
Section: Environmental Health Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…027008-14 128(2) February 2020 possible involvement of the promoter methylation of the TET2 gene. The methylation of CpG islands in the promoter region of genes is a well-known inhibitory mechanism for down-regulation of gene and protein expression (Figueroa et al 2010;Gong et al 2017). The hypermethylation of TET1 gene has been found in multiple primary tumors (Li et al 2016), and DNMT3A-mediated methylation of TET2 and TET3 promoters has been implicated in the induction of the epithelial-mesenchymal transition-like process and metastasis in melanoma (Gong et al 2017).…”
Section: Environmental Health Perspectivesmentioning
confidence: 99%
“…The methylation of CpG islands in the promoter region of genes is a well-known inhibitory mechanism for down-regulation of gene and protein expression (Figueroa et al 2010;Gong et al 2017). The hypermethylation of TET1 gene has been found in multiple primary tumors (Li et al 2016), and DNMT3A-mediated methylation of TET2 and TET3 promoters has been implicated in the induction of the epithelial-mesenchymal transition-like process and metastasis in melanoma (Gong et al 2017). TET2 promoter methylation has been implicated in lymphoblastic leukemia (Figueroa et al 2010;Musialik et al 2014) and has also been reported in a small fraction (4.4%) of myeloproliferative neoplasms (Chim et al 2010).…”
Section: Environmental Health Perspectivesmentioning
confidence: 99%
“…However, the sole use of DNMT inhibitors in melanoma treatment has yielded mixed results, which might be due to the heterogenicity of tumors and the overall epigenetic alterations. Moreover, reduced expression of TET2 in melanoma may provide novel options [ 88 89 ]. As discussed above, the DNA methylation status has been observed to be low in the neoplastic progression of carcinogenesis.…”
Section: Dna Methylation and Hydroxymethylationmentioning
confidence: 99%
“…Epithelial-mesenchymal transition (EMT) is a critical event for the initiation of tumor malignancy. During tumor progression, EMT can induce increased migration and invasion (Alonso et al, 2007;Voon et al, 2012;Gong et al, 2017), and the EMT-like process also plays a key role in melanoma malignancy (Alonso et al, 2007;Gong et al, 2017). Runx3 reportedly induces the epithelioid transformation of fibroblasts (Wotton et al, 2008).…”
Section: Discussionmentioning
confidence: 99%